2021
DOI: 10.1016/j.sjbs.2021.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic analysis of Rhynchophorus ferrugineus (Olivier) in Eastern Province, Saudi Arabia

Abstract: Red palm weevil (RPW) is the most aggressive date palm parasite in the Middle East, and especially in the Gulf region. Originated in Southeast Asia, this pest has been detected in the entire Arabian Peninsula, North Africa, Italy, Latin America, and other territories. It is important to local from obtrusive species, which help augmenting the pest control strategies. In the present study we collected 21 RPW samples from 21 different locations in the Eastern Province, Saudi Arabia to genetically characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…All RNAi/CRISPR techniques could also benefit from improved reference genomes and some knowledge of the genetics of invasive RPW populations. To this day, population genetics of the RPW are restricted to the use of a single/few markers, mostly mitochondrial genes and microsatellite loci [ 98 , 99 , 100 , 101 ]. In this context, whole-genome sequencing of multiple field-collected individuals from diverse locations would be an important step toward understanding RPW population history and genetic diversity.…”
Section: Opportunities and Challenges Of Practical Uses Of Rpw Omics ...mentioning
confidence: 99%
“…All RNAi/CRISPR techniques could also benefit from improved reference genomes and some knowledge of the genetics of invasive RPW populations. To this day, population genetics of the RPW are restricted to the use of a single/few markers, mostly mitochondrial genes and microsatellite loci [ 98 , 99 , 100 , 101 ]. In this context, whole-genome sequencing of multiple field-collected individuals from diverse locations would be an important step toward understanding RPW population history and genetic diversity.…”
Section: Opportunities and Challenges Of Practical Uses Of Rpw Omics ...mentioning
confidence: 99%
“…According to Pramudi et al (2013) that the slightest change in the reaction can change the amount and intensity of the amplification product so repeatability is difficult to maintain. (Muladno 2021) also added that RAPD cannot distinguish homozygous and heterozygous individuals because it is a dominant marker and difficult to detect small changes in the structure of DNA (Boomibalagan et al 2021;Sabit et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of studying genetic diversity among berry cultivars in selecting varieties with higher yields in fruits was previously reported [22]. It has been found that genetic variation was positive between genotypes and is useful for selecting appropriate groups for genomic mapping [14], and these genetic variations accumulated as a result of adaptation to different nutrient environments in artificial media, biotechnology methods that adopt bacteria to transfer the desirable traits in corps such as rice [38], thus stimulating physical, genetic variations as a result of adaptation, or non-adaptation to the components of the nutrient medium [10]. These findings support our results that showed different values of genetic stability in the studied media containing different types of plant growth regulators.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of genetics and technologies used in molecular biology, many researches have focused on biotechnological methods adopted in the study of laboratory-bred plants and comparison of their production of effective biological materials in wild species and the resulting cell strains, and these technologies proved their effectiveness in determining genetic patterns [10,11]. The previous findings showed different concentrations of cardiac glycosides in wild, cultivated, and bred species of digitalis plants [12].…”
Section: Introductionmentioning
confidence: 99%